The role of skin transplant in refractory venous ulcer treatment - Staniszewski, Ryszard; Stanišić, Michał; Winckiewicz, Marek; Majewski, Wacław; Zapalski, Stanisław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Chronic ulcer occurs in 0.2 to 2% of the Western Euro- pean population. Most common cause of the ulcers is the chronic venous insufficiency followed by hypertension in peripheral venous vessels and microcirculation of lower extremities. The evaluation of new more efficient and radical methods of treatment of large resistant to the treatment refractory ulcer is a need. Material and methods: In Clinic of General and Vascular Surgery between 2000-2004 54 patients underwent interventional treatment for venous ulcers (46 male, 8 female) aged from 52 to 78 (mean 68 y.o.). Duplex Doppler was performed in all patients for the evaluation of the pathology in arterial and venous system. Large infected ulcers were treated with the excision of granulation tissue and meshed skin grafts directly on the fascia. In other patients, when the ulcer was healed and granulation tissue prepared, the patients were admitted for skin transplant. The skin transplants were prepared with the Riverdin method in 15 patients and mesh grafts in 12 patients. All patients were immobilized for 7-10 days. The type of skin graft was chosen in regard of ulcer dimension and degree of the infection. Ulcers below 50 cm 2 were qualified for Riverdin graft, larger for the mesh graft. Patients were mobilized in compressive stockings. Results: In all patients the ulcers were healed during their stay in the Clinic. In 42 (78%) total healing was observed and in 12 (22%) 70-80% of the ulcer was healed. Following ambulatory treatment brought the complete healing of the ulcer within 3 weeks. The follow up was made every three months with the routine Doppler control for the venous system. The reoccurrence of the ulcer occurred In 8 patients (15%) of 49 (91%) of the observed patients. Recurrence of the ulcer occurred between 8-36 months, average 12 months. Conclusions: In our opinion Riverdin or meshed skin grafts are very useful in the treatment of patients with refractory venous ulcers. Skin grafts shorten the healing time and are well tolerated by the patients. Reduction of treatment costs is also significant.